2016
DOI: 10.1155/2016/1520685
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Folic Acid Supplementation in Pregnant Women by Estimation of Serum Levels of Tetrahydrofolic Acid, Dihydrofolate Reductase, and Homocysteine

Abstract: Background. Status of folic acid use in pregnant women of the hilly regions in North India was little known. This study was carried out to assess the folic acid use and estimate folate metabolites in pregnant women of this region. Materials and Methods. This cross-sectional study is comprised of 76 pregnant women, whose folic acid supplementation was assessed by a questionnaire and serum levels of homocysteine, tetrahydrofolic acid (THFA), and dihydrofolate reductase (DHFR) were estimated using Enzyme Linked I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Nearly 50% of all anaemia can be attributed to iron deficiency [1,2]. Folic acid is also a vital micronutrient required for the metabolism, foetal growth, and the development of the neural tube [3]. Globally, the estimated prevalence of anaemia among nonpregnant and pregnant women was 29% and 38%, respectively, whereas, in Africa, the estimated proportions were 37.8% and 46.3%, respectively [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nearly 50% of all anaemia can be attributed to iron deficiency [1,2]. Folic acid is also a vital micronutrient required for the metabolism, foetal growth, and the development of the neural tube [3]. Globally, the estimated prevalence of anaemia among nonpregnant and pregnant women was 29% and 38%, respectively, whereas, in Africa, the estimated proportions were 37.8% and 46.3%, respectively [2].…”
Section: Introductionmentioning
confidence: 99%
“…These include biological changes (menstrual period), undernutrition attributed to poverty, food insecurity, gender inequalities, inadequate knowledge of proper dietary practices, and increased iron and folic acid deficiency [5]. Furthermore, pregnant women experience increased micronutrient demand especially iron for the growth of foetus and metabolism which cannot be easily met by diet alone because of the poor intake and low absorption of iron [3].…”
Section: Introductionmentioning
confidence: 99%
“…Although DHFR enzyme levels have been analyzed in cancer cell cultures (Mishra et al , 2007), to our knowledge our study is the first to analyze the association of DHFR enzyme concentrations in RA patients with DHFR −829C-T genotypes. All of our patients had levels more than 6.1 ± 3.1 ng/mL, which suggests that patients with RA have DHFR enzyme overexpression relative to that seen in healthy populations (Naithani et al , 2016). Galbiatti et al (2013) found that DHFR gene expression levels in cancer cells dose-dependently increased with MTX treatment.…”
Section: Discussionmentioning
confidence: 59%
“…The majority of pregnant females and healthcare providers tend to ignore folic acid (FA) supplementation in the first trimester [ 2 ]. Very few studies have been conducted in India on the awareness of pregnant women regarding FA supplementation, providing comprehensive information about their current knowledge and its determinants [ 3 , 4 ]. Globally, the prevalence of NTDs among newborns is approximately 1-5/1000 live births with a 2%-3% risk of recurrence [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…There has been no such study in Chhattisgarh and eastern India, which assessed the awareness regarding FA supplementation among pregnant women. Furthermore, very few studies have estimated serum FA and vitamin B12 levels among pregnant women and assessed the correlation between them [ 4 , 11 ].…”
Section: Introductionmentioning
confidence: 99%